1990
DOI: 10.1016/0020-7292(90)90237-f
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of HIV antibody status and decisions to continue or terminate pregnancy among intravenous drug users

Abstract: We studied decisions to continue or terminate pregnancy among human immu-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 0 publications
4
27
1
1
Order By: Relevance
“…The finding of intent to procreate among adolescents and young adults with perinatally acquired HIV infection who are aware of their HIV diagnosis is consistent with other studies that found that knowledge of HIV status has no association with decisions to plan a pregnancy [22,23]. The significantly higher frequency of intent to have children among participants in our survey who perceived a low risk of maternal-to-child transmission compared to those who perceived it as high is consistent with other studies that reported higher desire to have children among women who believe in the efficacy of risk-reduction strategies [11].…”
Section: Discussionsupporting
confidence: 91%
“…The finding of intent to procreate among adolescents and young adults with perinatally acquired HIV infection who are aware of their HIV diagnosis is consistent with other studies that found that knowledge of HIV status has no association with decisions to plan a pregnancy [22,23]. The significantly higher frequency of intent to have children among participants in our survey who perceived a low risk of maternal-to-child transmission compared to those who perceived it as high is consistent with other studies that reported higher desire to have children among women who believe in the efficacy of risk-reduction strategies [11].…”
Section: Discussionsupporting
confidence: 91%
“…Mulheres UDI parecem engravidar com maior freqüência do que as não usuárias de droga injetável, fato atribuído ao uso inconsistente de preservativos, ou simplesmente à não utilização destes. Um estudo de Selwyn e col. 48 , entre mulheres UDI, revelou que 24% das mulheres HIV soropositivas engravidaram ao longo do período de seguimento no âmbito de um programa de tratamento, para uma proporção de 22% dentre as mulheres UDI não infectadas pelo HIV. O mesmo estudo mostrou que um número similar das gestantes, infectadas ou não, optaram pela interrupção da gravidez 48 .…”
Section: Transmissão Vertical Entre Mulheres Udiunclassified
“…Factors in¯uencing decisions about childbearing are com plex. Socio-cultural background, past reproductive history and policies concerning term ination of pregnancy together with m aternal H IV infection are likely to in¯uence decisions about child-bearing (Selwyn & Antoniello, 1993;Sunderland et al, 1992;Selwyn et al, 1989;Johnstone et al, 1990;Sherr, 1993;Kline et al, 1995). Perception of the risk of vertical transm ission based on local evidence m ay also affect decisions to have children.…”
Section: Discussionmentioning
confidence: 97%